EU anti-money laundering and counter-terrorism financing measures in context of electronic money institutions and payment processors - Zotova, Anna (Riga Graduate School of Law, 2018)
The purpose of the given research would be to analyze the current EU AML / CTF regime with regard to electronic money institutions and payment providers, detect the scope of legal norms and regulations, obliging them, identify potential loopholes and suggest additional measures to strengthen existing AML and CTF legal regimes with regard to such entities.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Electronic money institutions; European Union